ChemInform Abstract: A Metal‐Free Sulfenylation and Bromosulfenylation of Indoles: Controllable Synthesis of 3‐Arylthioindoles and 2‐Bromo‐3‐arylthioindoles. Issue 10 (7th March 2013) - Huang, Dayun; Chen, Jiuxi; Dan, Weixing; Ding, Jinchang; Liu, Miaochang; Wu, Huayue
Abstract The amount of NBS [cf.